Analysis of repeated high-intensity running performance in professional soccer - Carling, C.; Le Gall, F.; Dupont, G. (Journal of Sports Sciences, 2012)
The aims of this study were twofold: (1) to characterize repeated high-intensity movement activity profiles of a professional soccer team in official match-play; and (2) to inform and verify the construct validity of tests commonly used to determine repeated-sprint ability in soccer by investigating the relationship between the results from a test of repeated-sprint ability and repeated high-intensity performance in competition. High-intensity running performance (movement at velocities >19.8 km/h for a minimum of 1 s duration) was measured in 20 players using computerized time-motion analysis. Performance in 80 French League 1 matches was analysed. In addition, 12 of the 20 players performed a repeated-sprint test on a non-motorized treadmill consisting of six consecutive 6 s sprints separated by 20 s passive recovery intervals. In all players, most consecutive high-intensity actions in competition were performed after recovery durations =61 s, recovery activity separating these efforts was generally active in nature with the major part of this spent walking, and players performed 1.1 ± 1.1 repeated high-intensity bouts (a minimum of three consecutive high-intensity bouts with a mean recovery time =20 s separating efforts) per game. Players reporting lowest performance decrements in the repeated-sprint ability test performed more high-intensity actions interspersed by short recovery times (=20 s, P < 0.01 and =30 s, P < 0.05) compared with those with higher decrements. Across positional roles, central-midfielders performed more high-intensity actions separated by short recovery times (=20 s) and spent a larger proportion of time running at higher intensities during recovery periods, while fullbacks performed the most repeated high-intensity bouts (statistical differences across positional roles from P < 0.05 to P < 0.001). These findings have implications for repeated high-intensity testing and physical conditioning regimens.